Research on Factors Influencing Medical Insurance Cost in the US - He, Quanjing (Transactions on Economics, Business and Management Research, 2024)
After the COVID-19 epidemic, the growing concern over medical insurance cost and the factors that influence it are increasingly coming to the forefront. These factors include age, sex, body mass index, number of children, smoker or non-smoker and region. Therefore, this paper analyzes the impact of six factors on medical insurance costs by utilizing data on medical insurance expenses of 2,772 individuals in the US. The analysis employs a multiple linear regression model and the stepwise regression method. It is concluded that age, body mass index, number of children, smoker or non-smoker and region have a significant impact on medical insurance cost with the largest regression coefficients for age, body mass index and smoker or non-smoker. This shows that it is physiological factors that have the greatest impact and therefore it is recommended that people should better maintain good health in order to reduce medical insurance cost and save money.